1999
DOI: 10.1074/jbc.274.36.25371
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Host/Tumor Cell Interaction Activates Matrix Metalloproteinase 1 and Mediates Invasion through Type I Collagen

Abstract: Along with degradation of type IV collagen in basement membrane, destruction of the stromal collagens, types I and III, is an essential step in the invasive/metastatic behavior of tumor cells, and it is mediated, at least in part, by interstitial collagenase 1 (matrix metalloproteinase 1 (MMP-1)). Because A2058 melanoma cells produce substantial quantities of MMP-1, we used these cells as models for studying invasion of type I collagen. With a sensitive and quantitative in vitro invasion assay, we monitored th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 36 publications
(92 reference statements)
2
82
0
Order By: Relevance
“…In further support of such findings, a recent study showed that increased MMP-1 expression in human melanoma tumors correlated with tumor regression and a better clinical outcome (Nikkola et al, 2001). MMP-1 has also been reported to be a positive regulator of tumor invasion and keratinocyte migration (Benbow et al, 1999;Brinckerhoff et al, 2000;Dumin et al, 2001;Pilcher et al, 1997;Pilcher et al, 1998). Thus, MMP-1 and other MMPs appear to stimulate cell behaviors that are associated with tumor invasion and progression (Egeblad and Werb, 2002).…”
Section: Mmp-10 Zymogen Is Induced During Ec Morphogenesis and Is Actmentioning
confidence: 61%
“…In further support of such findings, a recent study showed that increased MMP-1 expression in human melanoma tumors correlated with tumor regression and a better clinical outcome (Nikkola et al, 2001). MMP-1 has also been reported to be a positive regulator of tumor invasion and keratinocyte migration (Benbow et al, 1999;Brinckerhoff et al, 2000;Dumin et al, 2001;Pilcher et al, 1997;Pilcher et al, 1998). Thus, MMP-1 and other MMPs appear to stimulate cell behaviors that are associated with tumor invasion and progression (Egeblad and Werb, 2002).…”
Section: Mmp-10 Zymogen Is Induced During Ec Morphogenesis and Is Actmentioning
confidence: 61%
“…MMP-1 mediates the invasion of melanoma cells through type I collagen in vitro (21,22), and this is largely attributed to the ability of MMP-1 to degrade the collagen surrounding the cells (27). To test the ability of each shRNA cell line to degrade type I collagen, cells were plated into an in vitro collagen destruction assay (24).…”
Section: Resultsmentioning
confidence: 99%
“…Melanoma expresses several different MMPs, and their expression pattern changes throughout the different stages of melanoma progression (17,18), with MMP-2, which degrades the type IV collagen of basement membrane, being frequently linked to an invasive phenotype (19,20). MMP-1 has not been well studied in melanoma progression, although its primary substrate, type I collagen, is a major component of the dermal layer of skin, and MMP-1 expression is necessary for melanoma cell invasion through synthetic ECMs in vitro (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…In a differentiated epithelial cell line (MadinDarby canine kidney cells), overexpressing proMMP-1 did not confer an invasive phenotype in an in vitro peritoneal invasion model or in a three-dimensional collagen matrix, perhaps because these cells did not express the proteinases needed to fully activate the latent enzyme (3,(12)(13)(14). However, when MMP-1 was overexpressed in the skin of transgenic mice, it increased their susceptibility to skin carcinogenesis (15).…”
Section: Introductionmentioning
confidence: 99%